Development of a single-domain antibody to target a G-quadruplex located on the hepatitis B virus covalently closed circular DNA genome - Figueroa, Gerardo B.; D'souza, Simmone; Pereira, Higor S.; Vasudeva, Gunjan; Figueroa, Sara B.; Robinson, Zachary E.; Badmalia, Maulik D.; Meier-Stephenson, Vanessa; Corcoran, Jennifer A.; van Marle, Guido; Ni, Yi; Urban, Stephan; et al. (Journal of medical virology, 2024)
To achieve a virological cure for hepatitis B virus (HBV), innovative strategies are required to target the covalently closed circular DNA (cccDNA) genome. Guanine-quadruplexes (G4s) are a secondary structure that can be adopted by DNA and play a significant role in regulating viral replication, transcription, and translation. Antibody-based probes and small molecules have been developed to study the role of G4s in the context of the human genome, but none have been specifically made to target G4s in viral infection. Herein, we describe the development of a humanized single-domain antibody (S10) that can target a G4 located in the PreCore (PreC) promoter of the HBV cccDNA genome. MicroScale Thermophoresis demonstrated that S10 has a strong nanomolar affinity to the PreC G4 in its quadruplex form and a structural electron density envelope of the complex was determined using Small-Angle X-ray Scattering. Lentiviral transduction of S10 into HepG2-NTCP cells shows nuclear localization, and chromatin immunoprecipitation coupled with next-generation sequencing demonstrated that S10 can bind to the HBV PreC G4 present on the cccDNA. This research validates the existence of a G4 in HBV cccDNA and demonstrates that this DNA secondary structure can be targeted with high structural and sequence specificity using S10.